The Instagrammable Hotel: A Sequential Explanatory Design Study of Hotel- and User-Generated Content - Christian Dragin-Jensen; Mia Post-Lundgaard; Oliver Schnittka (Tourism and Hospitality)
This paper examines Instagram’s increasing influence on the hotel industry, an area that remains under-researched from both consumer and hotel perspectives. Through a sequential explanatory design, combining a quantitative analysis of 1031 posts with qualitative interviews from hotel professionals, the research uncovers the types of content that resonate most with users and how hoteliers strategically leverage Instagram. The findings reveal which content formats, hotel attributes and post characteristics capture audience attention. Additionally, the study offers unique insights into Instagram’s distinct role compared to other social media platforms in the hotel industry. The study provides a novel definition of what makes a hotel “Instagrammable” from both consumer and industry viewpoints, offering valuable insights into how hotels can strategically harness Instagram to attract and engage their audience.